Liminalitas Sebagai Ide Penciptaan Karya Seni Lukis - Tonerin, Tonerin; Burhan, Mukhamad Agus (Institut Seni Indonesia Yogyakarta, 2025)
This final project explores the concept of liminality as the foundation for creating paintings, inspired by the artist's personal experience of living between Javanese and Sundanese cultures. The ambiguity of identity gives rise to existential uncertainty, which is expressed through visual exploration of symbols, metaphors, and liminal spaces. The creative process follows Graham Wallas’s model and employs the plakat technique using oil on canvas. The works adopt a metaphorical surrealism style, combining realistic representation with absurd symbols to evoke an ambiguous inner experience. These paintings aim to serve as a medium for reflecting on liminal experiences often overlooked in everyday life. Tugas Akhir ini mengangkat konsep liminalitas sebagai dasar penciptaan karya seni lukis, terinspirasi dari pengalaman personal penulis yang hidup di wilayah perbatasan budaya Jawa dan Sunda. Ketidakjelasan identitas memunculkan kegamangan yang diwujudkan dalam karya melalui eksplorasi simbol, metafora, dan ruang ambang. Proses penciptaan mengikuti model Graham Wallas dan menggunakan teknik plakat dengan cat minyak di atas kanvas. Gaya yang digunakan adalah surealisme metaforik, yang memadukan realisme dengan simbol absurd untuk menghadirkan pengalaman batin yang ambigu. Karya ini diharapkan menjadi media refleksi terhadap pengalaman liminal dalam kehidupan sehari-hari.